Analysis of the Gap Between the Polri Almatsus Blueprint and Operational Needs in the Meta-Globalization Era - Prabowo, Dikie; Nita, Surya; Gani, Yopik (Dinasti Research, 2025)
This creates new challenges for security institutions, including the Indonesian National Police (Polri), which are required to adjust their strategies, tactics, and special equipment (Almatsus) to address various threats and operational demands in this highly dynamic era. This study aims to analyze the factors causing the gap between the planning of special equipment (Almatsus) by Polri and the needs in the field in facing global challenges, as well as to analyze the impact of the gap between the Almatsus Blueprint and the reality of operational needs on the effectiveness of Polri's performance in maintaining security and order in the era of meta-globalization. This research employs a qualitative research method, using strategic management theory as the analytical lens. The findings reveal that the gap between the planning and needs of Polri’s special equipment (Almatsus) is caused by external factors, such as technological advancements and the dynamics of modern crime, as well as internal factors, including a lack of coordination, limited human resources, and inflexible planning. This results in a mismatch between what is planned and operational realities, negatively impacting Polri's effectiveness in maintaining security, especially in the era of meta-globalization. This gap can decrease operational effectiveness, personnel morale, and institutional image, as well as result in material losses due to inappropriate procurement.